Factors affecting renal scar development in children with spina bifida - Ozel, S. K.; Dokumcu, Z.; Akyildiz, C.; Avanoglu, A.; Ulman, I. (Karger, 2007)
Background/ Aims: Prevention of renal scarring is the main therapeutic goal in children with spina bifida. We aimed to determine factors affecting renal scar development in these patients. Materials and Methods: Records of 312 children admitted between 1994 and 2005 with spina bifida were reviewed. Age on admission, gender, presence of previous febrile urinary tract infections ( UTIs), vesicoureteral reflux ( VUR), and initial urodynamic findings were noted. Patients were grouped regarding presence/ absence of renal scars on DMSA scans. chi(2) and Student's t tests were used for statistical evaluation. Results: Seventy- two patients had renal scars on admission. Mean age was 4.62 +/- 4.59 years for patients without renal scars and 6.35 +/- 4.9 years for patients with scars. Male/ female ratio was 1: 1 in the scarless group and 1: 2 in the group with scars. Previous febrile UTI was present in 11 of 240 scarless patients in contrast to 7 out of 72 patients in the scar group ( p > 0.05). VUR was present in only 16.3% of cases without scars, whereas 36.1% of patients in the scar group had VUR. Detrusor overactivity and detrusor sphincter dyssynergia were observed in 67.1% of scarred patients, whereas this figure was 42.4% in the scarless group. The comparison of age on admission, gender, detrusor overactivity, and detrusor sphincter dyssynergia revealed significant differences between patients with and without renal scars. Conclusions: Late referral, female gender, overactive detrusor, and detrusor sphincter dyssynergia have detrimental effects on renal parenchymal function in spina bifida patients. Patient selection for aggressive treatment using these features may prevent renal parenchymal deterioration.
Keywords: kidney; risk factors; spina bifida